Diastereopure Synthesis of Novel Cyclohexane-Ring-Based Constrained Lanthionine and α-Methyllanthionine through an SN2 Reaction with a β-Bromoalanine as a Key Step - Gracia-Vitoria, Jaime; Carretero, Ángel; Osante, Iñaki; Cativiela, Carlos (Synlett, 2020)
Here we report the diastereopure synthesis of a novel protected lanthionine derivative substituted with a cyclohexane ring as well as the diastereopure synthesis of an α-methyllanthionine derivative. By starting from enantiopure α,β-cyclohexane-substituted cystine, or α-methylcysteine, we designed a straightforward route that permits the preparation of orthogonally protected modified lanthionines in diastereopure form. The key step of the methodology is the formation of a thioether bond through the use of an β-bromoalanine derivative. The strategy developed should be valuable in the preparation of a wide range of modified constrained lanthionines that might be finally attached to a peptide sequence, which would be especially useful in the syntheses of novel lantibiotics.
Keywords: lanthionines; cysteine; cystine; asymmetric synthesis; medicinal chemistry